The encyclopaedic dictionary of environmental change - Matthews, John A. (John Anthony) 1947- (SAGE, 2012)
'The Encyclopedic Dictionary of Environmental Change' covers changes affecting the earth over geological, intermediate and short timescales, including pre-Quaternary, Quarternary, Holocene, historical and current environmental changes.